A Bridge Over Turbulent Waters: Illustrating the Interaction Between Managerial Leaders and Facilitators When Implementing Research Evidence. Issue 1 (20th January 2016) - van der Zijpp, Teatske Johanna; Niessen, Theo; Eldh, Ann Catrine; Hawkes, Claire; McMullan, Christel; Mockford, Carole; Wallin, Lars; McCormack, Brendan; Rycroft‐Malone, Jo; Seers, Kate
ABSTRACT: Background: Emerging evidence focuses on the importance of the role of leadership in successfully transferring research evidence into practice. However, little is known about the interaction between managerial leaders and clinical leaders acting as facilitators (internal facilitators [IFs]) in this implementation process. Aims: To describe the interaction between managerial leaders and IFs and how this enabled or hindered the facilitation process of implementing urinary incontinence guideline recommendations in a local context in settings that provide long‐term care to older people. Methods: Semistructured interviews with 105 managers and 22 IFs, collected for a realist process evaluation across four European countries informed this study. An interpretive data analysis unpacks interactions between managerial leaders and IFs. Results: This study identified three themes that were important in the interactions between managerial leaders and IFs that could hinder or support the implementation process: "realising commitment"; "negotiating conditions"; and "encouragement to keep momentum going." The findings revealed that the continuous reciprocal relationships between IFs and managerial leaders influenced the progress of implementation, and could slow the process down or disrupt it. A metaphor of crossing a turbulent river by the "building of a bridge" emerged as one way of understanding the findings. Linking Evidence to Action: Our findings illuminate a neglected area, the effects of relationships between key staff on implementing evidence into practice. Relational aspects of managerial and clinical leadership roles need greater consideration when planning guideline implementation and practice change. In order to support implementation, staff assigned as IFs as well as stakeholders like managers at all levels of an organisation should be engaged in realising commitment, negotiating conditions, and keeping momentum going. Thus, communication is crucial between all involved.